New taxa of crickets (Orthoptera: Grylloidea: Phaloriinae, Phalangopsinae, Itarinae and Podoscirtinae) from Borneo (Brunei Darussalam and Sandakan) - Tan, Ming Kai; Japir, Razy; Chung, Arthur Y. C.; Wahab, Rodzay Bin Haji Abdul (Zootaxa, 2020)
Three new species were described from Borneo: Itara (Bornitara) spinosa sp. nov. and Aphonoides duri sp. nov. from Brunei and Varitrella (Cantotrella) suikei sp. nov. from Sandakan in Sabah. We describe the call of Varitrella (Cantotrella) suikei sp. nov. In addition to the new species descriptions, we also report new locality records of other recently discovered species: Borneloria spinosa Gorochov, 2018 in Belait (Brunei Darussalam), species of Anemozara Gorochov, 2014 in Brunei Darussalam and Terrozacla borneo Gorochov, 2014 in Belait.